Essentials of accounting for governmental and not-for-profit organizations - Copley, Paul A. (New York : McGraw-Hill/Irwin, 2011)
Copley's Essentials of Accounting for Governmental and Not-for-Profit Organizations, 10/e is best suited for those professors whose objective is to provide more concise coverage than what is available in larger texts. There is more comprehensive coverage of accounting for governmental and not-for-profit organizations than what is available in an advanced text but concise enough to be used effectively in a semester, quarter, or even a half term course focusing on just these areas
1. Introduction to accounting and financial reporting for governmental and not-for-profit organizations -- 2. Overview of financial reporting for state and local governments -- 3. Modified accrual accounting: including the role of fund balances and budgetary authority -- 4. Accounting for the general and special revenue funds -- 5. Accounting for other governmental fund types: capital projects, debt service, and permanent -- 6. Proprietary funds -- 7. Fiduciary (trust) funds -- 8. Government-wide statements, fixed assets, long-term debt -- 9. Accounting for special-purpose entities, including public colleges and universities -- 10. Accounting for private not-for profit organizations -- 11. College and university accounting-private institutions -- 12. Accounting for hospitals and other health care providers -- 13. Auditing, tax-exempt organization, and evaluating performance 14. Financial reporting by the federal government
Includes bibliographical references and index
Keywords: Administrative agencies -- United States -- Accounting; Nonprofit organizations -- United States -- Accounting